Αναφορές για τον Κοραή και το έργο του στον αγγλοσαξονικό κόσμο - Βλαχάκης Γιώργος Ν. (The Gleaner, 2011)
REFERENCES TO KORAIS AND HIS WORK IN THE ANGLO-SAXON WORLD This paper presents some of the most significant references to Adamantios Korais in the Anglo-Saxon world of the late 18th century and the 19th. Through these references, readers may garner a view of the image that Western scholars had of the intellectual movement in Greece before the revolution of 1821, as well as gaining an idea of the opinion of Anglo-Saxon scholarly circles about Korais and his work. This evidence is of some importance because it gives us a more complete picture of the status Greek scholars in general and Korais in particular held outside of the Greek-speaking world of the period. GEORGE N. VLAHAKIS